Bowel function, sexual function, and symptoms of pelvic organ prolapse in women with and without urinary incontinence. Issue 8 (10th April 2018) - Cameron, Anne P.; Smith, Abigail R.; Lai, H. Henry; Bradley, Catherine S.; Liu, Alice B.; Merion, Robert M.; Gillespie, Brenda W.; Amundsen, Cindy L.; Cella, David; Griffith, James W.; Wiseman, Jonathan B.; Kreder, Karl J.; et al.
Abstract : Aims: Bowel symptoms, pelvic organ prolapse, and sexual dysfunction are common, but their frequency among women with lower urinary tract symptoms (LUTS) has not been well described. Our aims were to describe pelvic floor symptoms among women with and without urinary incontinence (UI) and among subtypes of UI. Methods: Women with LUTS seeking care at six U.S. tertiary care centers enrolled in prospective cohort study were studied. At baseline, participants completed the Pelvic Floor Distress Inventory (PFDI‐20), Pelvic Organ Prolapse/Incontinence Sexual Questionnaire (PISQ‐IR), and PROMIS GI Diarrhea, Constipation, and Fecal Incontinence Scales. Results: Mean age among the 510 women was 56.4 ± 14.4 years. Women who reported UI ( n  = 420) had more diarrhea and constipation symptoms (mean scores 49.5 vs 46.2 [ P  = 0.01] and 51.9 vs 48.4 [ P  < 0.01], respectively) at baseline. Among sexually active women, mean PISQ‐IR subscale scores were lower among those with UI (condition specific: 89.8 vs 96.7, P  < 0.01; condition impact: 79.8 vs 92.5, P  < 0.01). Women with mixed urinary incontinence (MUI) ( n  = 240) reported more prolapse symptoms, fecal incontinence, and worse sexual function compared to those with stress urinary incontinence (SUI) and urgency urinary incontinence (UUI). Conclusions: Women presenting with LUTS with UI reported significantly worse constipation, diarrhea, fecal incontinence, and sexual function compared to women without UI. In women with UI, sexual function and pelvic organ prolapse (POP) symptoms were worse in those with MUI compared to SUI and UUI.